FAS‐mediated apoptosis impairment in patients with ALPS/ALPS‐like phenotype carrying variants on CASP10 gene. (15th July 2019) - Miano, Maurizio; Cappelli, Enrico; Pezzulla, Agnese; Venè, Roberta; Grossi, Alice; Terranova, Paola; Palmisani, Elena; Maggiore, Rosario; Guardo, Daniela; Lanza, Tiziana; Calvillo, Michaela; Micalizzi, Concetta; et al.
Summary: Autoimmune lymphoproliferative syndrome (ALPS) is a congenital disorder that results in an apoptosis impairment of lymphocytes, leading to chronic lymphoproliferation and autoimmunity, mainly autoimmune cytopenias. FAS gene defects are often responsible for the disease, the phenotype of which can vary from asymptomatic/mild forms to severe disease. More rarely, defects are associated to  other genes involved in apoptosis pathway, such as CASP10 . Few data are available on CASP10 ‐mutated patients. To date, two CASP10 mutations have been recognized as pathogenic (I406L and L258F) and others have been reported with controversial result on their pathogenicity (V410l, Y446C) or are known to be polymorphic variants (L522l). In this study, we evaluated apoptosis function in patients with an ALPS/ALPS‐like phenotype carrying CASP10 variants. Molecular findings were obtained by next generation sequencing analysis of genes involved in immune dysregulation syndromes. Functional studies were performed after inducing apoptosis by FAS‐ligand/TRIAL stimulation and analysing cell death and the function of CASP10, CASP8 and PARP proteins. We identified 6 patients with an ALPS ( n  = 2) or ALPS‐like ( n  = 4) phenotype, carrying I406L ( n  = 1), V410l ( n  = 2), Y446C ( n  = 1) heterozygous CASP10 variants or the L522l polymorphisms ( n  = 2) associated with another polymorphic homozygote variant on CASP8 or a compound heterozygous mutation on TNFRSF13C . Apoptosis was impaired in all patients showing that such variants may play a role in the development of clinical phenotype.